Normalization of the global far right : pandemic disruption? - Vieten, Ulrike M.; Poynting, Scott (Emerald Publishing Limited, 2022)
Exploring how the boundary between the extremist far right and centre-right parties and politics became blurred, Normalization of the Global Far Right: Pandemic Disruption deconstructs one of the most pressing issues of today: the rise of the far right. Taking a critical look at the 'normalisation' of far-right thinking underpinned by gendered racisms, Vieten and Poynting trace the emergence of transnational far right populist movements and how these have been shaped by European colonialism, white supremacy, and ideological legacies of the Empire alike.